2019
DOI: 10.1097/aln.0000000000002458
|View full text |Cite
|
Sign up to set email alerts
|

Positive End-expiratory Pressure and Mechanical Power

Abstract: EDITOR’S PERSPECTIVE What We Already Know about This Topic Positive end-expiratory pressure protects against ventilation-induced lung injury by improving homogeneity of ventilation, but positive end-expiratory pressure contributes to the mechanical power required to ventilate the lung What This Article Tells Us That Is New This in vivo study (36 pigs mechanically ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
1
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 20 publications
4
85
1
22
Order By: Relevance
“…MP is the energy delivered to the respiratory system over time, which is the product of the absolute proximal airway pressure and related changes in volume and respiratory rate [10]. Animal data showed that increasing MP was associated with an increase in lung edema and lung damage [11][12][13]. Furthermore, two studies in patients with and without ARDS found that MP computed during the first days of mechanical ventilation was independently associated with mortality, which rose significantly above a certain level of MP [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…MP is the energy delivered to the respiratory system over time, which is the product of the absolute proximal airway pressure and related changes in volume and respiratory rate [10]. Animal data showed that increasing MP was associated with an increase in lung edema and lung damage [11][12][13]. Furthermore, two studies in patients with and without ARDS found that MP computed during the first days of mechanical ventilation was independently associated with mortality, which rose significantly above a certain level of MP [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the monitored variables of ventilation that relate to total inflation pressure, active debate has developed as to whether the element with most influence is endinspiratory static (plateau) pressure or its difference from PEEP, known as the driving pressure (ΔP) [6][7][8]. PEEP bears a U-shaped relationship to VILI risk, with low levels tending to reduce atelectasis and distribute stress [9,10]. On the other hand, high PEEP sets an elevated platform from which widespread tidal overstretching of the parenchyma as well as hemodynamic compromise become increasingly likely [10].…”
Section: Sub-components and Thresholds Of Tidal Energymentioning
confidence: 99%
“…PEEP bears a U-shaped relationship to VILI risk, with low levels tending to reduce atelectasis and distribute stress [9,10]. On the other hand, high PEEP sets an elevated platform from which widespread tidal overstretching of the parenchyma as well as hemodynamic compromise become increasingly likely [10]. Finally, neither PEEP, plateau pressure, nor their difference (ΔP) reflect the dynamics and dissipated energy of the tidal cycle.…”
Section: Sub-components and Thresholds Of Tidal Energymentioning
confidence: 99%
See 1 more Smart Citation
“…These hemodynamic problems recede quickly after release of the recruiting pressure. Sustained high transpulmonary pressures have been shown to be potentially tissue damaging in both pre-injured rodents (39) and healthy pigs (40). The durability of benefit from the RM also depends on the tidal ventilation pattern (PEEP and tidal volume) that follows its application (24).…”
Section: The Place Of a Recruiting Maneuver (Rm) In Peep Selectionmentioning
confidence: 99%